Research on cam frequency-increasing hybrid piezoelectric electromagnetic energy harvester with center symmetric structure. (February 2022) - Zhou, Jianwen; He, Lipeng; Yu, Gang; Liu, Lei; Gu, Xiangfeng; Wang, Yuecheng; Cheng, Guangming
Abstract: This paper proposes a cam frequency-increasing hybrid piezoelectric electromagnetic energy harvester with center symmetric structure (C-HEH). The use of the cam structure allows the harvester to increase the efficiency of energy harvester per unit time, while the center symmetric structure of the entire harvester allows for maximum energy output in a limited size. This paper studies the influence of the number of cam protrusions and the length of the cylindrical permanent magnet on the output voltage signal at different rotation speeds. When the number of cam protrusions is 3 and the length of the cylindrical magnet is 10 mm, the maximum peak-to-peak voltages of the piezoelectric and the electromagnetic power generation unit are 53.74 V and 3.16 V, respectively. The effective value power of the hybrid energy harvester can be obtained as 1.49 mW. A series of application experiments were carried out to verify the performance of the C-HEH. The hybrid energy harvester can easily light up 86 light-emitting diodes (LEDs) lights and make the scientific calculators work stably after rectification. These results demonstrate the giant prospect of piezoelectric-electromagnetic energy harvesters for supplying wireless sensor networks and low-power electronic devices.